Environmental impact of the social-environmentalism - Dourojeanni, Marc (2020)
The social-environmentalism can be described as a hybrid conceptual current between the environmentalism –mostly based on ecology and economics– and, the humanism, rooted on social sciences, especially sociology and anthropology. The social-environmentalism calls itself "environmentalism with social awareness." At present, socio-environmentalism has largely replaced environmentalism and its techniques that, in many cases, even came to be seen as retrograde, as in the case of natural protected areas. But, this hybrid, as usual, is not fertile. It does not work well for society nor for the environment. In addition, socio-environmentalism is growingly very alike current radical anthropocentrism, which does not consider that the natural is transcendent. Both are equivalent to the ancient myth of the inexhaustible nature.